Pertumbuhan Diameter, Ketebalan dan Bobot Buah Melon (Cucumis melo L.) Akibat Pemberian Dosis Pupuk NPK dan Konsentrasi Pupuk Daun Growmore - Tripama, Bagus; Jalil, Abdul; Wahyudi, Ferdian A.; Wahyudi, Andri; Ananda, Pio T. (Jurusan Biologi FMIPA Universitas Cenderawasih, 2023)
Melon has high potential and economic value and has been developed in various fields such as plant breeding, cultivation technology, and the creation of new varieties. Proper cultivation and maintenance techniques are one of the efforts to increase melon crop production through fertilizing with the right type of fertilizer and dosage and concentration. Information on the use of NPK fertilizer and Growmore Fertilizer to increase the diameter, thickness, and weight of melon fruit has not been found. Therefore, this study aimed to increase the diameter, thickness, and weight of melon fruit. This research was expected to get a better diameter, thickness, and weight of melon. This research was conducted in the experimental garden of the Muhammadiyah University of Jember. Research implementation began in January 2023 with an altitude of ± 98 m asl. This study used a randomized block design (RBD) with two factors and three replications, namely: NPK fertilizer: P0 = 0 g/plant (control), P1 = 600 kg/ha (15 g/plant), P2 = 800 kg/ha (20 g /plant). Growmore leaf ertilizer N0 = 0 g/l (control), N1 = 3 g/l, N2 = 4 g/l (125 ml/plant). Observational variables consisted of: planted fruit weight (kg), fruit weight per plot (kg), fruit diameter (mm), and flesh thickness (mm). In the variables of planting fruit weight and fruit weight per treatment plot that gave the highest yields were P1 with yields of 1.14 kg and 7.52 kg, N2 with yields of 1.09 kg and 6.68 kg, and P1N2 interactions gave the highest yields of 1 .28 kg and 8.20 kg. The variable diameter of the treated fruit that gave the highest yield was P1 with a yield of (24.30 mm) N2 with a yield of (23.09 mm and the P1N2 interaction gave the highest yield of 127.89 mm. On the variable thickness of the treated fruit, the highest yield was P2 with a yield of (5.47 mm, N2 with a yield of (4.61 mm), and P1N2 interaction gave the highest yield of 38.00 mm. Key words: diameter; thickness; melon fruit; NPK; growmore